2016
DOI: 10.1049/iet-map.2014.0713
|View full text |Cite
|
Sign up to set email alerts
|

Numerical dosimetry of CDMA/GSM, DCS/PCS and 3G signal jammers

Abstract: In this study, numerical dosimetry of a code division multiple access (CDMA)/global system of mobile, digital cellular service (DCS)/personal communications service (PCS) and third generation signal jammer working with three antennas is presented. Three anatomical full human body models of different ages and gender exposed to the signal jammer electromagnetic (EM) waves at 900, 1800 and 2100 MHz, simultaneously, are numerically modelled using a high‐resolution finite‐difference time‐domain gridding; solved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Yahya et al [ 53 ] have performed in-silico simulations: a jammer with three antennas tuned on three different frequencies (i.e., 900 MHz, 1800 MHz, and 2100 MHz) has been tested with three different human models: Eartha, Ella (both from the Virtual Family [ 37 ]) and the visible human (VH) phantom, at four different distances between the jammer and the human model (20 cm, 50 cm, 100 cm, and 200 cm). By means of computational techniques, the SAR values normalized to an input power of 1 W have been calculated and the results showed that, at the shortest distance, the highest value of the whole-body averaged SAR was 6.90 × 10 −3 W/kg, found in the Eartha model, and at the greatest distance the whole-body averaged SAR decreased to 4.98 × 10 −5 W/kg in the VH model.…”
Section: Resultsmentioning
confidence: 99%
“…Yahya et al [ 53 ] have performed in-silico simulations: a jammer with three antennas tuned on three different frequencies (i.e., 900 MHz, 1800 MHz, and 2100 MHz) has been tested with three different human models: Eartha, Ella (both from the Virtual Family [ 37 ]) and the visible human (VH) phantom, at four different distances between the jammer and the human model (20 cm, 50 cm, 100 cm, and 200 cm). By means of computational techniques, the SAR values normalized to an input power of 1 W have been calculated and the results showed that, at the shortest distance, the highest value of the whole-body averaged SAR was 6.90 × 10 −3 W/kg, found in the Eartha model, and at the greatest distance the whole-body averaged SAR decreased to 4.98 × 10 −5 W/kg in the VH model.…”
Section: Resultsmentioning
confidence: 99%